Differential Signatures of Second Language Syntactic Performance and Age on the Structural Properties of the Left Dorsal Pathway - Yamamoto, Kayako; Sakai, Kuniyoshi L. (Frontiers in Psychology, 2017)
In adult second language (L2) acquisition, individual differences are considerably large even among people with similar experiences. The neural mechanisms underlying this variability would include structural plasticity of language-related pathways. To elucidate such neuroplasticity, we focused on the transitional period of adolescence, which is associated with certain plasticity towards maturation following the sensitive period of language acquisition (≤12 years old). The adolescent brain would thus be influenced by age-dependent factors, as well as performances in L2. Here we examined individual differences in L2 performances controlling the duration of experience to reveal the differential signatures of performances and age on the plasticity of structural properties in major language-related pathways. We recruited Japanese students at two ages, i.e., junior (age: 13–14) and senior (age: 16–17) high-school students, all of whom started to expose to English at age 12 or 13. We divided them into subgroups, so that either L2 performance [Junior (High)/Senior (Low)] or age [Senior (Low)/Senior (High)] was matched in group comparisons; the duration of L2 experience was also controlled between the Senior (Low) and Senior (High) groups. We then examined the thickness and fractional anisotropy (FA) of the dorsal and ventral pathways, i.e., the arcuate fasciculus (Arcuate) and inferior fronto-occipital fasciculus (IFOF), respectively, using semi-automatic methods for selecting regions without branches. Regarding FA in the left Arcuate, the Senior (High) group showed significantly higher FA than the other two groups, indicating performance-related group differences. Further, FA in the left Arcuate was selectively correlated with the accuracy of a syntactic task. Regarding the thickness of the left Arcuate, the Senior (High) and Senior (Low) groups showed significantly larger thickness than the Junior (High) group, indicating age-related group differences. These differential performance-related and age-related signatures were evident on the left Arcuate alone, in contrast to the right Arcuate that showed only mild differences in thickness, and to the bilateral IFOF that lacked either signature. Our results suggest that the left dorsal pathway continued to develop to adolescence, and that performance differences in a syntactic task can be predicted by its FA, independent of age and the duration of experience.